Answer:
1000
Step-by-step explanation:
you look very beautiful btw give me brainliest please ;)
Answer:
I don't know sorry for no answer
Answer:
c seems right
Step-by-step explanation:
Answer: b and d
Step-by-step explanation:
Since the roots are x=2 and x=6, we can write the equation as
![f(x)=a(x-2)(x-6)](https://tex.z-dn.net/?f=f%28x%29%3Da%28x-2%29%28x-6%29)
Substituting in the coordinates of the vertex,
![-4=a(4-2)(4-6)\\\\-4=-4a\\\\a=1](https://tex.z-dn.net/?f=-4%3Da%284-2%29%284-6%29%5C%5C%5C%5C-4%3D-4a%5C%5C%5C%5Ca%3D1)
So, the equation is ![f(x)=(x-2)(x-6)](https://tex.z-dn.net/?f=f%28x%29%3D%28x-2%29%28x-6%29)
On expanding, we get ![f(x)=x^2 - 8x+12](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E2%20-%208x%2B12)
Answer:
The equation of the line is,
![y = - \frac{2}{5} x - 1](https://tex.z-dn.net/?f=y%20%3D%20%20-%20%20%5Cfrac%7B2%7D%7B5%7D%20x%20-%201)
Step-by-step explanation:
First, you have to write it in a form of y = mx + b :
![2x + 5y = 15](https://tex.z-dn.net/?f=2x%20%2B%205y%20%3D%2015)
![5y = 15 - 2x](https://tex.z-dn.net/?f=5y%20%3D%2015%20-%202x)
![y = 3 - \frac{2}{5} x](https://tex.z-dn.net/?f=y%20%3D%203%20-%20%20%5Cfrac%7B2%7D%7B5%7D%20x)
![y = - \frac{2}{3} x + 5](https://tex.z-dn.net/?f=y%20%3D%20%20%20-%20%5Cfrac%7B2%7D%7B3%7D%20x%20%2B%205)
When both lines are parallel to each other, they will have to same gradient value. So the equation of the line is y = (-2/5)x + b. Next, you have to find the value of b by substutituting (-10,3) into the equation :
![y = - \frac{ 2}{5}x + b](https://tex.z-dn.net/?f=y%20%3D%20%20%20-%20%5Cfrac%7B%202%7D%7B5%7Dx%20%2B%20b%20)
![let \: x = - 10,y = 3](https://tex.z-dn.net/?f=let%20%5C%3A%20x%20%3D%20%20-%2010%2Cy%20%3D%203)
![3 = - \frac{2}{5} ( - 10) + b](https://tex.z-dn.net/?f=3%20%3D%20%20-%20%20%5Cfrac%7B2%7D%7B5%7D%20%28%20-%2010%29%20%2B%20b)
![3 = 4 + b](https://tex.z-dn.net/?f=3%20%3D%204%20%2B%20b)
![3 - 4 = b](https://tex.z-dn.net/?f=3%20-%204%20%3D%20b)
![b = - 1](https://tex.z-dn.net/?f=b%20%3D%20%20-%201)